2012
DOI: 10.1210/me.2011-1349
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol 3-Kinase-Binding Protein, PI3KAP/XB130, Is Required for cAMP-induced Amplification of IGF Mitogenic Activity in FRTL-5 Thyroid Cells

Abstract: We previously demonstrated that long-term pretreatment of rat FRTL-5 thyroid cells with TSH or cAMP-generating reagents potentiated IGF-I-dependent DNA synthesis. Under these conditions, cAMP treatment increased tyrosine phosphorylation of a 125-kDa protein (p125) and its association with a p85 regulatory subunit of phosphatidylinositol 3-kinase (p85 PI3K), which were suggested to mediate potentiation of DNA synthesis. This study was undertaken to identify p125 and to elucidate its roles in potentiation of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 38 publications
4
40
1
Order By: Relevance
“…In a recent study, Yamanaka et al found rat XB130 was associated with p85 subunit of PI3K, and they named it as PI3KAP. This interaction is essential to enhance cAMP-induced amplification of IGF mitogenic activity in FRTL-5 thyroid cells [27]. In the present study, interaction between XB130 and p85 was found in both thyroid and lung cancer cells.…”
Section: Discussionsupporting
confidence: 60%
“…In a recent study, Yamanaka et al found rat XB130 was associated with p85 subunit of PI3K, and they named it as PI3KAP. This interaction is essential to enhance cAMP-induced amplification of IGF mitogenic activity in FRTL-5 thyroid cells [27]. In the present study, interaction between XB130 and p85 was found in both thyroid and lung cancer cells.…”
Section: Discussionsupporting
confidence: 60%
“…Re-expression of PDE4D inhibited cell death, which suggests that PDE4D might be both a tumour promoter and a therapeutic target in certain cancers. These beneficial effects of reducing PDE-mediated cAMP hydrolysis should, however, be tempered, given that cAMP can promote the growth of certain carcinomas and that apparently inactivating mutations in some PDEs (for example, PDE8 and PDE11 ) can predispose to endocrine tumours 88,89 . The effects of PDE inhibitors on the permeability of the blood–brain barrier may also alter the effects of other therapeutic agents 90 .…”
Section: Biological and Pathological Roles Of Pdesmentioning
confidence: 99%
“…It includes AFAP [1], AFAP1L1 (actin filament associate protein 1 like 1) [2], and XB130 (also known as actin filament associated protein 1-like 2, AFAP1L2) [3]. They have been demonstrated to participate in the regulation of various signaling pathways by forming protein-protein and/or protein-lipid complexes [1], [4], and under certain circumstances these adaptor proteins can be involved in tumorigenesis [5], [6].…”
Section: Introductionmentioning
confidence: 99%